Potential and Development of Marine Tourism at Madasari Beach Pangandaran District, Indonesia - Annida, Shafira Bilqis; Riyanti Rahmawati; Faqih Baihaqi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Madasari Beach, a notable natural tourist destination in Pangandaran Regency, West Java, possesses the three essential components of tourism known as the 3A's: Attractions, Accessibility, and Amenities. This study serves as a preliminary investigation to describe the potential of Pantai Madasari in the context of marine tourism development. The method used is non-participatory observation. The findings reveal that while the attractions at Pantai Madasari are limited, there is significant room for improvement and development in accessibility. Additionally, the amenities at Madasari beach require enhancement in terms of quantity, cleanliness, and comfort